Defining the outcome of patients with delayed diagnosis of differentiated thyroid cancer. (27th May 2014) - Amit, Moran; Rudnicki, Yaron; Binenbaum, Yoav; Trejo‐Leider, Leonor; Cohen, Jacob T.; Gil, Ziv
<x xml:space="preserve">Abstract</x> Objectives/Hypothesis In the present study we sought to define the outcome of patients with delay in diagnosis and treatment (>1 year) of well‐differentiated thyroid carcinoma (WDTC) due to initial benign cytology (IBC). Study Design Retrospective medical record review and analysis of survival outcomes. Methods The records of 47 patients with delayed diagnosis of thyroid cancer were reviewed. In 38, surgery was performed for growing nodules and in nine due to malignant cytology during follow‐up. Median time to delayed surgery was 52 months (range, 13–205 months). Multivariate analysis was performed to assess variables associated with outcome. Results Most patients (32/47) underwent total thyroidectomy, whereas 15/47 had hemithyroidectomy. With a median follow‐up of 96 months (range, 12–184 months), the 5‐year disease‐free survival of these patients was 96%. Multivariate analysis showed that the outcome of these patients was not statistically different than that of patients (n = 162) who underwent immediate surgery for similar disease. Conclusions We show that patients with delayed diagnosis and treatment for WDTC due to IBC have excellent outcome. Level of Evidence 4 Laryngoscope, 124:2837–2840, 2014